A novel organic–inorganic hybrid phase transition compound based on 4-ethylmorpholine with switchable dielectric and luminescent properties. (16th December 2021) - Liu, Jing-Yuan; Ye, Si-Yu; Wan, Min; Wang, Yan-Ning; Tong, Liang; Chen, Li-Zhuang
Abstract : [4-Ethylmorpholine]2 MnCl4 shows a significant thermal hysteresis in the phase transition with switchable dielectric and luminescent properties. Abstract : Switchable dielectric materials are attracting tremendous interest due to their low cost of manufacture, environment protection and structural flexibility. However, most of them have a single function. Here, we report one switchable dielectric material, [4-ethylmorpholine]2 MnCl4, with a high phase transition temperature of 425 K based on 4-ethylmorpholine. What is more interesting is that this compound also has photoluminescence characteristics. Owing to the excellent switchable dielectric transition and efficacious photoluminescence, this study may extend the application of switchable dielectric materials in the field of luminescence and multifunctional devices.